If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y + -5 = 95 Reorder the terms: -5 + 10y = 95 Solving -5 + 10y = 95 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 10y = 95 + 5 Combine like terms: -5 + 5 = 0 0 + 10y = 95 + 5 10y = 95 + 5 Combine like terms: 95 + 5 = 100 10y = 100 Divide each side by '10'. y = 10 Simplifying y = 10
| 4x^2y^2-9x^2=0 | | 49x^2y^2+7x^2y+x^2=0 | | 343x^2y^3-x^2=0 | | 8x^2y^3+27x^2=0 | | .05x+40=.15x | | -3x+5x=-8+6+9x | | -16t^2+96t+176=0 | | 3x^5-13x^4-29x^3+83x^2+66x-30=0 | | x^4-2x^2(x-2)+x^2-4x+4= | | 24=18-2g | | t^2-6t-11=0 | | 44-4h=12 | | 2+4x=-16 | | x=(x+1)(x+3) | | 91-x=171 | | x=x+1x+3 | | x^2+8ix-16=0 | | 166=4(x+20) | | 75n+30=375 | | 2x+4x=2x+36 | | (3x-5)+x+201=125 | | 12(x-7)=26-2 | | (3x-5)x+201=125 | | z^2+zw+w^2=0 | | z^2-2zw+w^2=0 | | -4(x-6)=-10 | | x^2-ix+6=0 | | -2(x+3)=-2 | | 2(p+10)=4 | | 81y^3-16y=0 | | 6(m-6)=5 | | 9y^3-4y^2=0 |